Transcription factors associated with leaf senescence in crops - Bengoa Luoni, Sofia Ailin; Astigueta, Francisco; Nicosia, Salvador; Moschen, Sebastian; Fernandez, Paula Del Carmen; Heinz, Ruth Amelia (MDPI, 2020)
Leaf senescence is a complex mechanism controlled by multiple genetic and environmental variables. Different crops present a delay in leaf senescence with an important impact on grain yield trough the maintenance of the photosynthetic leaf area during the reproductive stage. Additionally, because of the temporal gap between the onset and phenotypic detection of the senescence process, candidate genes are key tools to enable the early detection of this process. In this sense and given the importance of some transcription factors as hub genes in senescence pathways, we present a comprehensive review on senescence-associated transcription factors, in model plant species and in agronomic relevant crops. This review will contribute to the knowledge of leaf senescence process in crops, thus providing a valuable tool to assist molecular crop breeding.